1984
DOI: 10.1177/0272431684044002
|View full text |Cite
|
Sign up to set email alerts
|

Picking up the Pieces: The Effects of Parental Divorce on Adolescents with Some Suggestions for School-Based Intervention Programs

Abstract: Four aspects of the effects of divorce on adolescents are examined in this review. First, some of the recent changes that have taken place in the American family are examined, specifically changes in the number of divorces. Second, the effects of divorce on adolescent development are reviewed, especially possible consequences on intellectual performance and academic achievement. Also examined are the effects of divorce on personality development and social relations. Third, differences in adolescents' reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…This high involvement of noncustodial parents in the lives of children contrasts with research evidence that a substantial proportion of noncustodial fathers in sole-custody families ceases to exercise access to children over the years (Burns, 1980;Montemayor, 1984), a situation to which the attitudes of custodial mothers can sometimes contribute (Fulton, 1979). Furstenberg and Nord (1985), moreover, found that fathers from low socioeconomic status families, a group highly represented in this research, were even more likely to lose contact with noncustodial children.…”
Section: Discussioncontrasting
confidence: 90%
“…This high involvement of noncustodial parents in the lives of children contrasts with research evidence that a substantial proportion of noncustodial fathers in sole-custody families ceases to exercise access to children over the years (Burns, 1980;Montemayor, 1984), a situation to which the attitudes of custodial mothers can sometimes contribute (Fulton, 1979). Furstenberg and Nord (1985), moreover, found that fathers from low socioeconomic status families, a group highly represented in this research, were even more likely to lose contact with noncustodial children.…”
Section: Discussioncontrasting
confidence: 90%
“…These studies suggest that differences between dyads may outweigh structural effects of age and gender. Family variables that may infl uence sibling confl icts include divorce (Lamb & Sutton-Smith, 1982;MacKinnon, 1989;Montemayor, 1984), family size (Bossard & Boll, 1956), and levels of family violence (Martin, Schumm, Bugaighis, Jurich, & Bollman, 1987).…”
Section: This Study Examined Sibling Confl Ict and Relationship Qualimentioning
confidence: 99%
“…Exposure to certain specific life events has been shown to be negatively associated with problems in school performance. In particular, parental divorce has been associated with lower academic achievement (Amato & Keith, 1991; Boyd & Parish, 1985; Cherian, 1989; Guidubaldi, Perry, & Cleminshaw, 1984; Guidubaldi, Perry, Cleminshaw, & Mcloughlin, 1983; Hofmann & Zippco, 1986; Lindner, Hagan, & Brown, 1992; Monetmayor, 1984). In addition, death of a family member has also been negatively associated with children’s adjustment and school performance (Anthony & Koupernik, 1973; Felner, Ginter, Boike, & Cowen, 1981).…”
mentioning
confidence: 99%